2018
DOI: 10.3390/socsci7020030
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Civil Society Actors and Functions: On the Limitations of International Frameworks for Fragile States

Abstract: Over the past three decades, there has been a steady increase of funds by the international community to support civil society organizations (CSOs) in fragile states. Surprisingly, this growing attention has not strengthened local civil society landscapes in a way that it would lead to processes of social transformation. On the contrary, civic freedom and space is shrinking around the globe. In analyzing prominent international aid-effectiveness frameworks and donor strategies towards civil society, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
“…As Table 1 shown, we collected data from the six groups of stakeholders and then we placed them into five categories: None or few (0-20), not too much (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), neutral (41-60), partial (61-80), and very much (81-100). Among the 2563 responses related to the DAC, 62 people (2.4%) realized that the Afghan Government has no or few DACs to influence the development process of the Aynak Copper Mine, and 524 (20.4%) considered that there is not too much the DAC of the Afghan Government can do with the development of the Aynak Copper Mine.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…A violent conflict context is often faced with problems of limited resources, lack of infrastructures, absence or limited social services and multiple demands among others (Bruck et al, 2011). The empowerment of women under these constraints would require support from all actors such as the civil society, NGOs, and other development partners (Datzberger & Nguyen, 2018). Determination and efforts by various actors in tackling gender inequalities by employing economic empowerment strategies represent 'smart economics' which considers business as a tool for transformation (Roberts & Soederberg, 2012).…”
Section: Women Empowerment and Gender Equalitymentioning
confidence: 99%